Study on Producing Iron Ore Concentrate by Removing Sulphur from Pyrite Cinder with Nitric Acid Leaching - Shi, Zhaozhong; Han, Yanxia; Zhan, Guirong (Asian Journal of Chemistry, 2014)
Pyrite cinder is obtained by roasting the pyrite at 700-800 °C, so activity of the iron oxides is weak. Based on its weak activity property, nitric acid extraction of pyrite cinder is first used to remove the impurities such as S, CaO and Al2O3 and meanwhile, less than 10 % of the iron is dissolved into liquid. Most iron is enriched into acid leaching residue and the liquid are to be treated further. Orthogonal test shows that the optimal condition for leaching the cinder is concentration 5 mol L-1, the time is 1 h, temperature 50 °C and excess coefficient is 15. By this time, desulphurization degree is over 99 %, and iron leaching rate is less than 10 %. In the optimal technical condition, the sulphur content of pyrite cinder leaching slag is 0.03 %. It is in line with iron ore concentrate requirements (sulphur content is less than 0.10 %). To reveal the mechanism of this process, the phase transformation of the process were studied by X-ray diffractometer.